ANALISIS PENENTUAN PRIORITAS VARIABEL KLASTER INDUSTRI GENTENG UNTUK PENYUSUNAN STRATEGI PENGEMBANGAN KLASTER DENGAN MENGGUNAKAN ANALISA FAKTOR (STUDI KASUS INDUSTRI GENTENG DI KAB. JEMBER) - Djumhariyanto, Dwi (ROTOR, 2011)
The presence of roof tile companies in Tamansari - Wuluhan - Jember has not shown the existence of synergies between companies and with other elements in order to improve innovation and business efficiency. This was reflected in most of the production process to the marketing of roof tile products that are still performed as an individual company. In other words, the concentration of roof tile companies in Tamansari stopped only to the extent of an industrial roof tile. Whereas, by making a group of roof tile companies in a certain area allows for collaboration between companies as well as with other elements in these area to improve business efficiency as well as the creation of a new innovation related to the roof tile industry. This researh aimed at identifying cluster variables of roof tile industry that will provide competitive advantage for the roof tile industry, and determine the cluster variables priorities that can be used as a reference to arrange a cluster development strategy in the future. Determination of the cluster variables based on the concept of Porters Diamond Model. Roof tile industry cluster variables identified are: The Quality of Labor, Capital Access, Transportation Facilities, Telecommunication Facilities, Excellent Quality of Roof Tile, Suppliers Companies, Industrial Equipment Provider Companies, Roof Tile Buyer Companies, Financial Institutions, Transportation Companies, Distributors of Roof Tile Companies, Roof Tile Business Associations, Companies Strategy, Organizational Structure, Similar Companies, Job Training Centers, Universities, Corporate Tax, Legal and Quality Standards. Determination of the cluster variable priority to cluster development strategy using factor analysis, with the following results: Related and Supporting Industries Factor with variables as follow: Suppliers Companies, Industrial Equipm[1]ent Provider Companies, Roof Tile Consumer Companies, Financial Institutions, Transportation Companies, Roof Tile Distribution Companies, Roof Tile Business Associations; Factor Condition Factor with variables as follow: The Quality of Labor, Capital Access, Transportation Facilities, Telecommunication Facilities; The Role of Government Factor with variables: Employment Training Centers, Universities, Corporate Tax, Legal and Quality Standards; and Firm Strategy, Structure and Rivalry Factor which the variables: Companies Strategy, Organizational Structure, Similar Companies. Keywords: competitiveness, diamond model, industrial cluster, Â small and medium enterpris 1 Staf Pengajar Jurusan Teknik Mesin Fakultas Teknik Universitas Jember Â